The impact of industry 4.0 on supply chains - Lança, Ana Patrícia Franco Martins (2019)
The Fourth Industrial Revolution, known as Industry 4.0 (I4.0), is fundamentally changing the way businesses operate from product development to sales. Yet, research usually focuses on its impact on production or logistics alone and little research has been done on how the supply chains (SC) of the future will look like. In this work project, an analysis of the impact of I4.0 on SC was developed from the review of published literature, with the inclusion of small case studies that served as concrete examples of this impact. From this, a vision for the future of SC was developed.